Ocypus (Matidus) primoriensis Smetana, a new species from the Russian Far East (Coleoptera, Staphylinidae, Staphylinini) - Smetana, Aleš; Grebennikov, Vasily (Zootaxa, 2008)
In a paper dealing with the Chinese species of the subgenera Ocypus Leach, 1819 s. str. and Matidus Motschulsky, 1860, the senior author (Smetana 2007) commented that, in addition to Ocypus coreanus (J. Müller, 1925), an additional, undescribed species occurs in the Russian Far East. Recently, the junior author collected a long series of specimens of this undescribed species in the southernmost part of the Sikhote-Alin mountain range. This material provides the basis for the present paper, in which the new species is described, illustrated and compared to O. coreanus.